Mosque-Based Economic Empowerment through Agricultural Buyouts in the Perspective of Hifz al-Mal - Fitria; Khoirul Anwar; Sokhikhatul Mawadah (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2026)
This study aims to analyze mosque-based community economic empowerment through the Borong Hasil Tani Program of Nurul ’Ashri Mosque using the maqashid al-shari’ah approach, particularly hifz al-mal. This research employed a qualitative approach using a normative–empirical method through observation, in-depth interviews with mosque administrators, farmers, congregants, and beneficiary institutions, and documentation. The results indicate that the program helps maintain farmers’ income by absorbing agricultural products during periods of price decline through a direct purchasing mechanism supported by community funds and distributed through vegetable bazaar schemes, consignment services, and vegetable charity programs. This mechanism reflects the implementation of hifz al-mal through the productive circulation of community funds (rawaj), transparent governance (wuduh), protection of farmers’ income stability (hifz), sustainability of agricultural product distribution (thabat), and transactional justice through price deliberation (‘adl). These findings indicate that mosques have the potential to function as strategic institutions in protecting farmers’ economic welfare and strengthening local food security. The implications of this study highlight the importance of strengthening managerial capacity and multi-stakeholder collaboration to replicated mosque-based empowerment models across regions.